The effects of six sprint interval training sessions on muscle oxygenation and swimming performance in untrained swimmers - Dalamitros, Athanasios A.; Tzivanis, Dimitrios; Martín-Rodríguez, Alexandra; Semaltianou, Eleni; Mavridis, Georgios; Manou, Vasiliki (Frontiers in Sports and Active Living, 2024)
The current study examined the changes in muscle oxygenation values and swimming performance after six sessions of sprint interval training during a three-week period in untrained swimmers. Twelve swimmers of both genders (age: 23.5 ± 5.6yrs) executed the twice-weekly experimental training protocol (EXP, n = 12), consisting of a 4 × 50 m front-crawl swimming (repeated sprint training—RST) with maximal intensity, and 2 min of passive recovery in between, after a short in-water warm-up. The control group (CON, n = 9) performed a continuous swimming set (200 m) at 120 b pm−1, with the same weekly frequency. Performance times in two maximum swim trials (400 m: T400 and 50 m: T50), muscle oxygenation of the deltoid muscle (SmO2) immediately after T400 and T50, 1-min heart rate recovery (HRR1) after T400, T50, and swim strokes during both swim trials (S/T400, S/T50) were assessed. For the EXP group, T400 improved by 2.4 (p = 0.011). In contrast, T50 presented no significant improvement (1%, p > 0.05). SmO2 decreased at T400 (5.5%, p = 0.017) and increased at T50 (3.7%, p = 0.030). HRR1 improved after T400 (7.9%, p = 0.002), T50 (4.6%, p = 0.005) and RST (9.6%, p = 0.002). S/T400 and S/T50 remained relatively unchanged (p > 0.05). The CON group presented no significant changes in any of the variables examined. In conclusion, six sprint interval training sessions can improve aerobic capacity over a 3-week training period, as indicated by the enhanced T400 performance and the reduced HRR1 values, in previously trained swimmers. Finally, the sensitivity of the near-infrared spectroscopy method to detect short-term training-induced changes is highlighted.